Microwave filters for communication systems fundamentals, design and applications - Cameron, Richard J.; Kudsia, Chandra M.; Mansour, Raafat R. (Wiley, 2018)
The Second Edition of this book provides a description of systems requirements and constraints for microwave filters, fundamental considerations in the theory and design of microwave filters, and the use of EM techniques to analyze and optimize filter structures